Reduced Palatability in Drug-Induced Taste Aversion: I. Variations in the Initial Value of the Conditioned Stimulus - Lin, Jian-You (2012)
Like illness-inducing agents (e.g., lithium chloride), drugs of abuse also suppress intake of a taste solution. To explore the nature of this drug-induced intake reduction, in the current study three aqueous stimuli with different initial values served as the conditioned stimuli (CSs) that were paired with a standard dose of amphetamine in a voluntary intake procedure and lick patterns were analyzed. Consistent with earlier studies, amphetamine significantly reduced intake of all three CSs (quinine, sodium chloride and orange odor). In contrast to studies that analyze orofacial responses, we found that lick cluster size was significantly lowered by amphetamine, indicating that the psychoactive drug induced a conditioned change in CS palatability.